2005
DOI: 10.1093/eurheartj/ehi074
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel administration prior to coronary artery bypass grafting surgery: the cardiologist's panacea or the surgeon's headache?

Abstract: Pre-operative clopidogrel exposure increases the risk of haemostatic re-operation and the requirements for blood and blood product transfusion during, and after, CABG surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(58 citation statements)
references
References 31 publications
0
55
0
3
Order By: Relevance
“…In these studies, it was shown that dual antiplatelet therapy increased the risk of postoperative blood loss and receipt of blood transfusions following CABG, but there were no significant differences in terms of surgical mortality or outcomes. [22][23][24] One study showed that patients on dual antiplatelet therapy who underwent vascular, orthopaedic, and visceral surgical procedures had a higher chance of receiving a blood transfusion than controls on monotherapy (43% vs 39%). 25 These studies suggest that dual antiplatelet therapy in the perioperative period increases postoperative bleeding rates, but does not influence postoperative morbidity or mortality.…”
Section: Patients On Dual Antiplatelet Therapymentioning
confidence: 99%
“…In these studies, it was shown that dual antiplatelet therapy increased the risk of postoperative blood loss and receipt of blood transfusions following CABG, but there were no significant differences in terms of surgical mortality or outcomes. [22][23][24] One study showed that patients on dual antiplatelet therapy who underwent vascular, orthopaedic, and visceral surgical procedures had a higher chance of receiving a blood transfusion than controls on monotherapy (43% vs 39%). 25 These studies suggest that dual antiplatelet therapy in the perioperative period increases postoperative bleeding rates, but does not influence postoperative morbidity or mortality.…”
Section: Patients On Dual Antiplatelet Therapymentioning
confidence: 99%
“…Die Therapie der KHK durch Stentimplantation mit konsekutiver, oft dualer Thrombozytenaggregationshemmung zur Reduktion der "In-stent-Thrombose" erhöht einerseits das Risiko einer postoperativen Blutung [37]. Andererseits haben Patienten mit symptomatischer KHK (neben weiteren kardiovaskulären Risiken) ein hohes Risiko für ein perioperatives akutes Koronarsyndrom (PACS; [22]).…”
Section: Perioperative Behandlung Von Patienten Mit Khk Und Koronarstunclassified
“…Interessanterweise konnten Operateure bei Karotisthrombendarteriektomien anhand des Blutungsverhaltens nicht zwischen Patienten unter ASS-Medikation und einer Placebo-Gruppe differenzieren [10]. Für das Blutungsrisiko unter kombinierter Thrombozytenaggregationshemmer-Therapie mit ASS und Clopidogrel liegen nur Untersuchungen bei kardiochirurgischen Eingriffen vor, die ebenfalls keine erhöhte perioperative Mortalität zeigen [8]. Für nichtkardiochirurgische Eingriffe in der Allgemein-, Gefäß-und Unfallchirurgie wurde lediglich ein um 4% erhöhter Transfusionsbedarf unter ASS und Clopidogrel beschrieben [19].…”
Section: Introductionunclassified